Case Report: Hydroxychloroquine-induced generalized pustular psoriasis in a pediatric patient with systemic lupus erythematosus - Wang, Xue; Dong, Linlin; Qiu, Hui; Xu, Yihuai; Kong, Linxiaoyu; Zhou, Weiran (Frontiers in Pediatrics, 2025)
Hydroxychloroquine (HCQ) therapy is the main treatment for systemic lupus erythematosus (SLE); however, rare adverse effects, including generalized pustular psoriasis (GPP), have been predominantly reported in adults. We herein report the first case of GPP caused by HCQ in a pediatric SLE patient. A 7-year-old girl with SLE developed fever, hepatic dysfunction, and disseminated pustules 3 weeks after starting HCQ. Histopathological examination revealed the characteristic features of GPP, including epidermal hyperkeratosis with parakeratosis, pustule formation above the stratum spinosum and acanthosis. Neutrophils and lymphocytes were observed in the superficial and mid-dermal vascular plexuses. HCQ therapy was discontinued, and the patient received methylprednisolone, intravenous immunoglobulin, meropenem, and hepatoprotective therapy. After 9 days of treatment, the pustules had largely resolved and inflammatory markers had returned to normal. This unprecedented pediatric observation underscores HCQ as a potential trigger for GPP in pediatric patients with SLE and highlights the importance of immediate HCQ discontinuation for optimal outcome. Interleukin-17 and interleukin-36 cytokine pathways may synergistically contribute to pathogenesis, suggesting a role for targeted therapies.